EFFECTIVENESS OF IMPROVING TRADITIONAL PHARMACOLOGY KNOWLEDGE AMONG TRADITIONAL MEDICINE PRACTITIONERS THROUGH A CONTINUING MEDICAL EDUCATION TRAINING MODEL AT THE TUE TINH INSTITUTE OF MEDICINE AND PHARMACY THROUGH (Vietnam Journal of Community Medicine, 2026)
Objective: (1) To describe the characteristics of traditional medicine health workers attending the continuing medical education course at Tue Tinh Institute of Medicine and Pharmacy Research in 2025; (2) To assess the effectiveness of knowledge improvement in traditional medicine pharmacy among participants after the training course.Method: A pre-post interventional study was conducted on 242 trainees participating in continuing medical education courses on traditional pharmacology at the Tue Tinh Institute of Medicine and Pharmacy Research from September 2024 to March 2025. Data were collected before and after training, including knowledge of medicinal material identification, processing, and clinical application.Results: Before training, most trainees’ knowledge of medicinal material identification, processing, and application was at average-poor levels (> 70%). After training, the proportion achieving good markedly increased. The mean total post-training score significantly improved from 4.24 ± 1.78 to 8.68 ± 1.37. Participants with certificates or professional licenses achieved significantly higher scores (p
Keywords: Traditional medicine, continuing medical education, CME, traditional pharmacology.